Development of Interactive Digital Teaching Materials for Geometric Transformation Based on Ethno-STEM of Jombangan Culture to Enhance Students' Visual-Spatial Thinking Ability - Farabi, Muhammad Al; Masamah, Ulfa; Hidayat, Dayat (Jurnal Pendidikan Matematika, 2025)
Understanding geometric concepts often requires strong visual–spatial thinking skills, studies showed that internalizing visual-spatial thinking skills can be a solution in geometry learning. This study aims to develop interactive digital teaching materials for geometry transformation based on Ethno-STEM of Jombangan culture that are valid, practical and effective in helping improve students' visual-spatial thinking ability. The cultural aspects highlighted in this study are the unique traditional batik and historic temples of Jombang Regency.The research employed the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. Data collection techniques used observation, interview, questionnaire and test. Data analysis was carried out through quantitative and qualitative data. The results of the study showed that the developed materials demonstrated high validity with an average expert validation score of 85.90% (content, material, language, and learning aspects), high practicality with an average score of 91.31% (from practitioners and student responses), and moderate effectiveness indicated by a paired-sample t-test (sig. (1-tailed) = 0.000 < 0.05) and an average N-gain of 0.528. These findings suggest that the Ethno-STEM–based interactive materials are valid, practical, and effective for improving students’ visual–spatial thinking skills in geometry learning. Pemahaman konsep geometri sering kali menuntut kemampuan berpikir visual-spasial yang baik, penelitian menunjukkan bahwa menginternalisasi kemampuan berpikir visual-spasial dapat menjadi solusi dalam pembelajaran geometri. Penelitian ini bertujuan untuk mengembangkan bahan ajar digital interaktif geometri transformasi berbasis Ethno-STEM budaya Jombangan yang valid, praktis, dan efektif dalam membantu meningkatkan kemampuan berpikir visual-spasial siswa. Budaya yang diangkat berupa batik dan candi khas kabupaten Jombang. Metode penelitian ini menggunakan model pengembangan ADDIE yang meliputi tahap Analysis, Design, Development, Implementation, dan Evaluation. Teknik pengumpulan data menggunakan observasi, wawancara, angket, dan tes. Analisis data dilakukan melalui data kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa produk yang dikembangkan memiliki validitas tinggi dengan persentase rata-rata keseluruhan dari penilaian ahli materi, bahan ajar, bahasa, dan pembelajaran sebesar 85,90%; kepraktisan tinggi dengan rata-rata penilaian dari validator praktisi dan respon peserta didik sebesar 91,31%; serta efektivitas sedang dalam meningkatkan kemampuan berpikir visual-spasial peserta didik, dibuktikan melalui uji paired sample t-test dengan nilai sig. (1-tailed) = 0,000 < 0,05 dan rata-rata N-gain sebesar 0,528. Dengan demikian, bahan ajar digital interaktif berbasis Ethno-STEM budaya Jombangan dinyatakan valid, praktis, dan efektif untuk digunakan dalam pembelajaran geometri guna meningkatkan kemampuan berpikir visual-spasial siswa.